Synthesis of Copper Oxide Nanoparticles Using Plant Leaf Extract of Catha edulis and Its Antibacterial Activity. (24th November 2020) - Andualem, Worku Wubet; Sabir, Fedlu Kedir; Mohammed, Endale Tsegaye; Belay, Hadgu Hailekiros; Gonfa, Bedasa Abdisa
Abstract : Development of green technology is generating interest of researchers towards ecofriendly and low-cost methods for biosynthesis of nanoparticles (NPs). In this study, copper oxide (CuO) NPs were synthesized using a copper nitrate trihydrate precursor and Catha edulis leaves extract as a reducing and capping agent during the synthesis. The biosynthesized CuO NPs were characterized using an X-ray diffractometer (XRD), scanning electron microscopy-energy-dispersive X-ray spectroscopy (SEM-EDS), transmission electron microscope (TEM), Ultraviolet visible spectroscopy (UV-Vis), and Fourier transform infrared (FTIR) spectroscopy. XRD characterization confirmed that the biosynthesized CuO NPs possessed a good crystalline nature which perfectly matched the monoclinic structure of bulk CuO. Furthermore, the results obtained from SEM and TEM showed that the biosynthesized CuO NPs were spherical in shape. EDS characterization of the biosynthesized NPs also indicated that the reaction product was composed of highly pure CuO NPs. Moreover, the antimicrobial activities of different concentrations of CuO NPs synthesized using Catha edulis extract were also tested. Accordingly, the result showed that the highest zone of inhibitions measured were for CuO NPs synthesized using 1 : 2 ratios at 40 mg/ml solution concentration and observed to be 22 ± 0.01 mm, 24 ± 0.02 mm, 32 ± 0.02 mm, and 29 ± 0.03 mm for S. aureus, S. pyogenes, E. coli, and K. pneumonia, respectively.